Proposal of Marketing Mix for a Company Selling Tile Drill Bits - Spišáková, Tereza; Karlíček, Miroslav, 1979-; Bruyndonckx, Steven; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
The objective of this study is to propose changes within marketing mix of tile drill bits of Company X that would have a positive impact on product's revenues. To reach this goal a combination of analysis of internal and external secondary and qualitative analysis in a form of semi-structured interviews and expert judgement technique were conducted. The qualitative part of the research was executed with Company's X HUB product managers, who are considered to be experts on a given research topic. Based on the research author proposed to extend the length of tile drill bits portfolio with six additional diameters and to include additional accessories such as an adapter and starter kit with a dust collector that would create a full system for easy and convenient drilling into tiles. Within pricing author suggested to apply current pricing model also on the new parts of the portfolio since it was identified as adequate. Additionally, focus on Company’s X chain of stores and internal sales force as primary sales channels was recommended in order to create attention towards the product. In order to ensure the effectiveness of the promotional campaign, combined launch with complementary tool and the iconic Company’s X case for starter kit was proposed. All the outcomes of the study are detailly described in conclusions part of this thesis.
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses